Schizophrenia - Kahn, René S.; Meyer-Lindenberg, Andreas (Nature reviews. Disease Primers, 2015)
Schizophrenia is a complex disorder that debuts early in adolescence with cognitive and social dysfunction, followed many years later by psychosis. Alongside greater insight into disease mechanisms, Kahn and colleagues argue for applying current knowledge more effectively.